Study on the mechanical properties of embankment soil under long-term immersion conditions - Zhang, Kun; Feng, Di; Wang, Zhikui (Frontiers in Materials, 2023)
During flood season, embankments are often submerged in high water levels for extended periods, leading to deterioration in their soil mechanics performance and increasing the risk of slope instability and other hazards. In order to investigate the changes in mechanical properties of embankment slopes during long-term water immersion, direct shear tests were conducted on disturbed clay samples taken from the embankments at Jiangxinzhou in Nanjing, Jiangsu Province, China. Scanning electron microscopy, chemical composition analysis, and laser particle size analysis were conducted on samples taken at different immersion periods. Results showed the stress-strain curves of the soil and the corresponding changes in cohesion and internal friction angle values under different immersion periods. Results indicate that, the shear strength of the soil gradually decreases with the increase of immersion time, while the cohesive force and internal friction angle gradually decrease as well. This suggests that immersion has a softening effect on the shear strength of the soil.During the initial stage of immersion, the cohesive force significantly decreases. As the immersion time increases, the colloidal particles (soluble salt) rapidly dissolves, the microstructure of the soil is destroyed, the coarse particles in the soil further disperse and disintegrate, and the content of refined and sticky particles increases, resulting in a change in the shear strength of the soil.1 This is a provisional file, not the final typeset article Luoshui Town. Due to the erosion of floodwaters, more than 250 meters of the embankment collapsed, resulting in an economic loss of more than 4 million.Existing literature has shown that soil strength is a critical parameter in assessing slope stability